Impact of pesticides on farmer health and the rice environment : (Kluwer Academic Publishers, 1995)
The book covers the various aspects of the use of pesticides, their behavior, degradation, and impacts in wetland ricefields, and presents the results of surveys conducted in the Philippines and Thailand. It includes both bibliographic reviews and selected aspects of the experimental results of a research project on pesticide impacts in wetland ricefields. The first phase of the `Pesticide Impact' project was developed in the Philippines from 1989 to 1991. It was a multidisciplinary/collaborative approach involving scientists from IRRI, NRI (England), ORSTOM (France), UPLB (Philippines) who studied the effects of pesticides on the environment and on farmers' health, and the economical aspects of their use.